PKM Life Skill Menciptakan Wirausaha Baru Bengkel Sepeda Motor Bagi Masyarakat Tunakarya Kelurahan Parupuk Tabing Kecamatan Koto Tangah Kota Padang - Saputra, Hendra Dani; Nasir, M.; Setiawan, Dedi; Purwanto, Wawan; Muslim, Muslim; Putra, Rido (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2021)
The number of motorcycle users in the city of Padang is not proportional to the number of motorcycle repair service providers. Especially in Parupuk Tabing Village, Koto Tangah District, Padang City, the increase in the number of motorcycles is not proportional to the number of existing motorcycle repair shops. The opportunity to create a motorcycle workshop entrepreneur in this area is very promising.Life skill training for motorcycle mechanics for unemployed people aims to generate an entrepreneurial spirit by creating new entrepreneurs for motorcycle repair shops independently, and also providing assistance in the form of basic equipment to create new entrepreneurs for motorcycle repair shops.The implementation of PKM activities is carried out with the obligation to comply with health protocols in the Jondul 1 field, RW XVI, Parupuk Tabing Village, Koto Tangah District, Padang City, West Sumatra. The number of unemployed people who will take part in this training are 30 people. The implementation method approach used is (1) the lecture and question and answer method (2) the discussion method (3) the practical method, and (4) the guidance and evaluation method.The results of the training showed a high level of interest, participation and activeness of participants in participating in the training.